Association of Serum Uric Acid and Parkinson’s Disease: A Case Control Study (Bangladesh Journal of Neuroscience, 2016)
Background: Recent studies have provided evidence that uric acid (UA) is suspected to play a neuro-protective role in Parkinson’s disease (PD). Uric acid is a natural antioxidant that may reduce oxidative stress, a mechanism thought to play a role in the pathogenesis of PD. This study aimed to evaluate whether the serum UA level was associated with PD in a relatively small population of Bangladeshi patients.Materials and methods: An observational prospective case control Study was conducted in Neurology of Sir Salimullah Medical College & Mitford Hospital including both the male and female wards during July 2012 to December 2013. Serum uric acid were determined from 40 PD patients and compared with 70 age and sex matched control; following the uric acid colorimetric method, the serum creatinine (Scr) levels were also measured to reduce the bias caused by possible differences in renal excretion function. Data were analyzed with software SPSS 16 and statistical descriptive methods (mean percentage, SD) and t-test.Result: In this study, 22 men (55%) and 18 women (45%) with PD were evaluated. The mean serum uric acid in patients was 3.7±0.97 and in the control group was 5.32±0.44. This difference was statistically significant (p=0.001). Also, the mean serum uric acid in both men (3.48±0.98) and women (4.1±1.17) in patients group was statistically lower than both men (5.39±0.46) and women (5.17±0.35) in control group.(p=0.001).Conclusion: This present study showed a positive association between low serum UA and PDBangladesh Journal of Neuroscience 2016; Vol. 32 (2): 68-73